1995
DOI: 10.1128/aac.39.2.525
|View full text |Cite
|
Sign up to set email alerts
|

Right-sided endocarditis caused by Staphylococcus aureus in drug abusers

Abstract: A prospective, open, and randomized study of right-sided endocarditis caused by Staphylococcus aureus in drug abuse patients is reported. The following parenteral treatments were compared. Group A patients were treated with 2 g of cloxacillin every 4 h and 1.5 mg of gentamicin per kg of body weight every 8 h for 2 weeks. Group B patients were treated with teicoplanin at 10 mg/kg/12 h on the 1st to 3rd days, 6 mg/kg/12 h on the 4th to 7th days, and 7 mg/kg/24 h on the 8th to 28th days. Drug abusers with bactere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 21 publications
0
13
0
3
Order By: Relevance
“…Standardowy 4-6-tygodniowy schemat terapii należy wdrożyć w następujących sytuacjach: -powolna odpowiedź kliniczna lub mikrobiologiczna (> 96 h) na leczenie antybiotykami [426]; -IZW prawej części serca powikłane niewydolnością prawej komory, wegetacjami > 20 mm, ostrą niewydolnością oddechową, przerzutowymi ogniskami septycznymi poza płucami (w tym ropniakiem opłucnej) lub powikłaniami pozasercowymi, np. ostrą niewydolnością nerek [426]; -leczenie antybiotykami innymi niż benzylopenicyliny odporne na penicylinazy [437]; -IVDA z ciężką immunosupresją (liczba limfocytów CD4 < 200 komórek/μl) z objawami lub bez objawów AIDS [438]; -obecność dodatkowo IZW lewej części serca.…”
Section: Leczenie Przeciwdrobnoustrojoweunclassified
“…Standardowy 4-6-tygodniowy schemat terapii należy wdrożyć w następujących sytuacjach: -powolna odpowiedź kliniczna lub mikrobiologiczna (> 96 h) na leczenie antybiotykami [426]; -IZW prawej części serca powikłane niewydolnością prawej komory, wegetacjami > 20 mm, ostrą niewydolnością oddechową, przerzutowymi ogniskami septycznymi poza płucami (w tym ropniakiem opłucnej) lub powikłaniami pozasercowymi, np. ostrą niewydolnością nerek [426]; -leczenie antybiotykami innymi niż benzylopenicyliny odporne na penicylinazy [437]; -IVDA z ciężką immunosupresją (liczba limfocytów CD4 < 200 komórek/μl) z objawami lub bez objawów AIDS [438]; -obecność dodatkowo IZW lewej części serca.…”
Section: Leczenie Przeciwdrobnoustrojoweunclassified
“…Ninety-four percent of the 50 patients treated were cured with this regimen. Table 3 summarizes the studies published between 1988 and 2001 [26,[34][35][36][37]38••] with a 2-week course of nafcillin or cloxacillin plus an aminoglycoside (usually gentamicin) for the therapy of noncomplicated right-sided MSSA endocarditis in IVDAs. Overall, 209 patients have been treated, with an overall cure rate of greater than 90%.…”
Section: Advances In Antibiotic Therapymentioning
confidence: 99%
“…The standard 4-week regimen must be used in the following situations: 1) slow clinical or microbiologic response (> 96 hours) to the initial antibiotic therapy [28•,44]; [34] Clo + Gen 12 12 0/0 0 Torres-Tortosa et al [35] Clo + Amk 72 67 4/0 1 Miró [26] Clo + Gen 20 19 0/1 0 Fortún et al [36] Clo + Gen 8 7 1/0 0 Ribera et al [37] Clo + Gen 36 31 [46] demonstrated that oral antibiotic treatment with ciprofloxacin plus rifampin during 4 weeks was as effective as the recommended 4-week regimen with oxacillin plus gentamicin. This oral regimen may be a reasonable alternative to parenteral therapy in some patients.…”
Section: Exclusion Criteria For 2-week Course Of Combination Therapy mentioning
confidence: 99%
“…There is evidence that ␤-lactam therapy is better than glycopeptides for MSSA bacteremia from both randomized controlled trials (RCTs) (104,105,107) and observational studies (108)(109)(110)(111)(112)(113)(114)(115)(116)(117)(118). Vancomycin and daptomycin are currently the only antibiotics that are approved by the U.S. Food and Drug Administration (FDA) for MRSA bacteremia and right-sided IE.…”
Section: Outcomes and Managementmentioning
confidence: 99%